Relevant Aspects on Teaching Probability and Statistics in Basic General Education - Marianela Alpízar-Vargas; José Pablo Barrantes-Quirós; Helen Bolaños-González; Michael Céspedes-López; Evelyn Delgado-Carvajal; Dylana Freer-Paniagua; Erick Ricardo Padilla-Mora; María Fernanda Víquez-Ortiz (Revista Electrónica Educare)
Probability and Statistics were included in the Basic General Education curricula by the Ministry of Public Education (Costa Rica), since 1995. To analyze the teaching reality in these fields, a research was conducted in two educational regions of the country: Heredia and Pérez Zeledón. The survey included university training and updating processes of teachers teaching Statistics and Probability in the schools. The research demonstrated the limited university training in these fields, the dissatisfaction of teachers about it, and the poor support of training institutions to their professional exercise.